Contemporary management of TMJ involvement in JIA patients and its orofacial consequences. Issue 1 (December 2016) - Niibo, Priit; Pruunsild, Chris; Voog-Oras, Ülle; Nikopensius, Tiit; Jagomägi, Triin; Saag, Mare
Abstract Juvenile idiopathic arthritis is the most common chronic rheumatic condition during childhood. Temporomandibular joint arthritis is frequently asymptomatic. When it takes place during childhood, it may affect condylar growth; therefore, these children are at risk of unfavorable long-term outcomes from the associated joint damage. The etiology is not completely understood, but it is considered as multifactorial with both genetic and environmental factors involved. The standardized examination and imaging protocols serve important purpose to diagnose temporomandibular joint (TMJ) arthritis not only to establish an early interventional strategy but also to assess craniofacial growth and the progression of signs and symptoms in those patients. Although the treatment of juvenile idiopathic arthritis (JIA) has changed dramatically over the last decades due to new therapeutic options, TMJ arthritis still can develop during the course of the disease. In clinical experience, TMJs appear to respond less well to the standard of care used to treat other joints. More individualized approach to the patient's treatment serves as the main goal of personalized medicine. It could be achieved by adopting new methods of medical imaging such as conebeam computer tomography as well as developing reliable biomarkers which may assist with predicting disease type, course, or severity and predicting response to medication. This article provides an overview of current information on orofacial complications in JIA and its management. Based on information provided in this review, more precise diagnosis, proper tools for recognizing people at risk, and more efficient treatment approaches could be implemented. This may lead to more personalized treatment management strategies of TMJ complications of JIA patients.